Molecular identification of Trichoderma sp. Margodadi isolate and its potential against Phytophthora capsici causing foot rot of black pepper - Prasetyo, Joko; Evizal, Rusdi; Maryono, Tri; Ginting, Cipta; Juniar, Nur Baitullah (Jurnal Hama dan Penyakit Tumbuhan Tropika, 2024)
Trichoderma has the potential to suppress fungal pathogens and thus control plant diseases, including Phytophthora foot rot, which is the most devastating disease of black pepper in Lampung. Identification of a microorganism can not only rely on its morphological characteristics, but it is also necessary to identify it molecularly at the species level. This research was aimed at identifying the fungus Trichoderma sp. Margodadi isolates at the species level and to know the potential of Trichoderma sp. Margodadi isolates and their secondary metabolites to control P. capsici. This research was conducted from March to November 2021 at the Laboratory of Plant Disease, Department of Plant Protection, and the Laboratory of Agricultural Biotechnology, Faculty of Agriculture, University of Lampung. Identification of Trichoderma was done by morphological characteristics and molecular methods. The ability of Trichoderma to suppress P. capsici was tested by dual culture. The effect of secondary metabolites on the growth of P. capsici was determined in vitro at concentrations of 0% (control), 10%, 20%, 30%, and 40%. The experimental design used was a completely randomized design consisting of five treatments repeated five times. The data obtained from the test were analyzed using ANOVA, followed by the LSD test at 5%. The results of this study showed that Trichoderma sp. Margodadi isolate had a close relationship with Trichoderma asperellum and had the ability as an antagonist to inhibit the growth of P. capsici up to 47.23%, and the secondary metabolites produced could inhibit the growth of P. capsici up to 72.53% with the best concentration of 40%.